The Foreigner, the Other, the Homeless: Challenges to the Golden Rule - Abbarno, John (Bollettino Filosofico, 2019)
The twenty-first century has witnessed a rise in the number of global homeless. People are escaping their impoverished homelands with their families for security and peace in a country that promises a better life. The United States and countries in Europe are viewed as safe harbors but they resist adequate entry due to the increased numbers of people. The predominant perspective toward this phenomenon has been through political lens but it belies a deep-seated philosophical problem of humanity. This entails a convenience of interacting with strangers as classified groups and not persons of value. This paper examines the concept of “foreigner”, as a particular kind of “other”, the homeless. The Golden Rule alone is not sufficient to morally address this humanitarian crisis. The paper makes a case for a moral role of empathy that could reestablish the original ideal expressed by the Golden Rule. Keywords: Foreigner, Other, Homeless, Golden Rule, Humanitarian crisis